A high HEMSTOP bleeding score is a major independent risk factor for postpartum hemorrhage: a prospective cohort study - Florian Deleu; Sophie Nebout; Edith Peynaud-Debayle; Laurent Mandelbrot; Hawa Keita (BMC Pregnancy and Childbirth)
Abstract Background Postpartum hemorrhage (PPH) is a common yet potentially serious complication of delivery. Recently, the HEMSTOP bleeding score has emerged as a tool for detecting preoperative inherited bleeding disorders. Our objective is to investigate its relevance within the obstetrical context for predicting PPH occurrences among unselected pregnant women. Methods Prospective cohort study conducted in a tertiary maternity hospital between 2014 and 2016 including women without any known bleeding disorder nor antithrombotic therapy who completed the HEMSTOP questionnaire before delivery. Primary outcome was primary PPH ≥ 500 mL following delivery. We studied the bleeding score ranging from zero to seven both as a continuous and an ordinal variable. We used multivariable analysis with adjustment on PPH risk factors. We also estimated the measures of the bleeding score prognostic accuracy. Results PPH occurred in 116 of 2536 women (4.6%). Elevated bleeding scores were associated with increased PPH risk (adjusted RR = 1.58; 95% CI, 1.23 to 2.02; P < 0.001 for a continuous score) demonstrating a progressive rise in risk alongside score escalation (adjusted RR = 1.58; 95% CI, 1.01 to 2.46 for a score of one, adjusted RR = 2.11, 95% CI 0.86 to 5.20 for a score of two and adjusted RR = 7.20, 95% CI 2.54 to 20.41 for a score of three compared with a score of zero; P < 0.001). The area under the curve for the bleeding score accuracy in predicting PPH was 0.56 [95% CI 0.52 to 0.61]. Conclusions The HEMSTOP bleeding score is weakly predictive of PPH. Women scoring ≥ three are at high risk of PPH.